The Relevancy of the Past - Tkacheva, Marina (project baikal, 2016)
The article observes the book “Irkutsk and its Citizens” by S. I. Medvedev issued in 2015. The article features the key topics of the book and characterizes its visual material and the possibility to use this issue for city space investigations.